2021
DOI: 10.1007/s00268-021-06388-7
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Probiotics Administration Before Liver Resection in Patients with Liver Disease: A Randomized Controlled Trial

Abstract: Background By inhibiting the growth of pathogenic bacteria and modulating the local intestinal immune system, probiotics may reduce bacterial translocation and systemic endotoxaemia, factors partially responsible for post‐operative complications following liver resection for hepatocellular carcinoma in patients with cirrhosis. Methods Patients with resectable hepatocellular carcinoma developed in the setting of chronic liver disease were prospectively divided into two equal‐sized groups: one receiving probioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The same influence of perioperative symbiotics on IL-6 levels was reported in the study of Usami et al who used symbiotics on liver cancer patients before hepatectomy [ 72 ]. However, in a recent RCT where patients with hepatocellular carcinoma received probiotics preoperatively, the IL-6 levels after hepatectomy were not statistically different between the control and the probiotic group [ 92 ]. In another RCT with obese patients having a gastric bypass, the perioperative use of probiotics decreased the levels of CRP, IL-6, and TNF-α in the probiotic group after surgery, but this reduction was statistically important only for TNF-α [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same influence of perioperative symbiotics on IL-6 levels was reported in the study of Usami et al who used symbiotics on liver cancer patients before hepatectomy [ 72 ]. However, in a recent RCT where patients with hepatocellular carcinoma received probiotics preoperatively, the IL-6 levels after hepatectomy were not statistically different between the control and the probiotic group [ 92 ]. In another RCT with obese patients having a gastric bypass, the perioperative use of probiotics decreased the levels of CRP, IL-6, and TNF-α in the probiotic group after surgery, but this reduction was statistically important only for TNF-α [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…A small RCT showed that colorectal cancer patients who received preoperative probiotics had significantly lower levels of plasma endotoxin, D-lactic acid, interleukin-6, and C-reactive protein and higher levels of IgG and IgA immunoglobulins after colectomy compared to the control group [ 75 ]. On the other hand, Roussel et al, recently, showed that there is no regulatory effect of preoperative probiotics on serum endotoxins as they did not find a statistically important difference between the control group and the liver cancer patients who took probiotics before hepatectomy [ 92 ]. In a recent study, the use of probiotics in gastric cancer patients only postoperatively (starting 3–5 days after gastrectomy) showed a notable effect in reducing the inflammatory process provoked by surgery and enhancing existing immunity.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with hepatic cancer, Roussel et al found no significant difference in all postoperative complications and mortality after two weeks of oral probiotics versus placebo [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other microbiota species, namely Atopobium vaginae , Selenomonas sputigena , and Faecalibacterium prausnitzii , have been identified as diagnostic biomarkers of malnutrition and poor prognosis in colorectal cancer [ 21 ], whereas Clostridium butyricum may have great potential for improving the nutritional status of malnourished patients [ 22 ]. Concerning probiotics, a 2-week probiotic intervention in patients with hepatocellular carcinoma did not improve postoperative complications and mortality [ 36 ]. Nevertheless, infectious complications and LOS were significantly lower in patients with colorectal cancer receiving a 1-week symbiotic intervention [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, three randomized-controlled trials are ongoing to understand the effect of probiotics in hepatobiliary tumors, including CCA and HCC (Table 10). The results showed that TNFα and interleukin 1β levels significantly increased in patients who were orally administered the mixed probiotics (containing Bifidobacterium lactis, Lactobacillus plantanum, and Lactobacillus salivarius) in the post-operative periods, thereby supporting the use of probiotics to modulate the immune response in reducing complications of infections in patients [182]. However, there is no current evidence to support the mechanism of probiotics modulating gut microbiota in CCA patients, and, therefore, more clinical studies are needed to prove the therapeutic benefits of probiotics in CCA patients.…”
Section: Probiotics In Cca Preventionmentioning
confidence: 87%